2020
DOI: 10.1097/ta.0000000000002687
|View full text |Cite
|
Sign up to set email alerts
|

Large volume transfusion with whole blood is safe compared with component therapy

Abstract: BACKGROUND Transfusion with uncrossmatched cold-stored low-titer group O-positive or -negative whole blood (WB) in civilian trauma has been investigated as an alternative to component therapy but only in limited volumes. To our knowledge, this is the first analysis of the safety and efficacy of large volume transfusion of patients with trauma with WB. METHODS This is a retrospective cohort analysis comparing trauma patients resuscitated with component t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 19 publications
1
35
0
Order By: Relevance
“…Initially, the data that were generated on the use of LTOWB surrounded implementation strategies in the pre‐hospital and in‐hospital phases of the resuscitation, 1–3 as well as data on the serological safety of transfusing LTOWB to non‐group‐O recipients 4–6 . As the use of LTOWB began to increase in the US and in other countries, 7–9 several studies have attempted to determine whether the use of LTOWB in trauma resuscitation resulted in a survival benefit compared with the transfusion of conventional components (CCT) using different study methodologies and have found conflicting results 10–15 . For example, in a single‐center analysis of 198 injured LTOWB patients who received a median of one unit either pre‐hospital or early in their in‐hospital course, 30‐day mortality was reduced in a multivariate logistic regression model compared to 152 conventional component recipients 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, the data that were generated on the use of LTOWB surrounded implementation strategies in the pre‐hospital and in‐hospital phases of the resuscitation, 1–3 as well as data on the serological safety of transfusing LTOWB to non‐group‐O recipients 4–6 . As the use of LTOWB began to increase in the US and in other countries, 7–9 several studies have attempted to determine whether the use of LTOWB in trauma resuscitation resulted in a survival benefit compared with the transfusion of conventional components (CCT) using different study methodologies and have found conflicting results 10–15 . For example, in a single‐center analysis of 198 injured LTOWB patients who received a median of one unit either pre‐hospital or early in their in‐hospital course, 30‐day mortality was reduced in a multivariate logistic regression model compared to 152 conventional component recipients 11 .…”
Section: Introductionmentioning
confidence: 99%
“…A multivariate analysis performed on the American College of Surgeons Trauma Quality Improvement Program (TQIP) database during the calendar years of 2015 and 2016 also revealed that 24‐h and in‐hospital mortality was significantly reduced among the 280 patients who had received a median (IQR) of 1 (1–1) unit LTOWB compared to 8214 patients who received only component therapy 12 . Conversely, three other observational single‐center studies in which the LTOWB patients received a median (IQR) of 2 (1–3), 6.5 (3–11), and 2 (1–2) units of LTOWB, respectively, 13–15 did not demonstrate a mortality benefit compared to the patients who received CCT. A recent meta‐analysis of studies reporting 24‐h and 30‐day/in‐hospital survival among LTOWB recipients compared to those resuscitated with conventional components also did not find a survival advantage to the receipt of LTOWB 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In a third study, an analysis of a large national database found that trauma patients receiving a combination of WB plus component therapy had significantly reduced 24‐h and in‐hospital mortality compared with patients receiving component therapy alone 12 . In contrast, three other observational, single‐center studies with median WB doses of 2, 6.5, and 2 units did not show a decrease in mortality 13‐15 . Finally, a meta‐analysis of studies that measured 24‐h and 30‐day in‐hospital survival failed to demonstrate a survival advantage to patients treated with WB compared with CT 17 …”
mentioning
confidence: 97%
“…There have been multiple studies comparing LTOWB to component therapy that have sought to demonstrate the potential benefits of LTOWB with varying results. These studies have used different methodologies and varying doses of WB 10‐15 . A 2020 review of WB studies concluded that there is substantial evidence that WB is safe and feasible, but it has not been shown to be superior to component therapy in any large or randomized studies 16 .…”
mentioning
confidence: 99%
See 1 more Smart Citation